The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.5897/jdae2013.0535
|View full text |Cite
|
Sign up to set email alerts
|

Trend and determinants of multidimensional poverty in rural Nigeria

Abstract: Government continues to initiate programmes to address the challenge of poverty in Nigeria.This paper investigates the poverty levels over time using the multidimensional approach and estimates its determinants; using the National Living Standard Survey data of 2004 and 2010. The Alkire-Foster methodology and the Logit model were employed for analysis. The result showed that 70% of rural households are headed by males, are still in their economically active years and practice agriculture. Also, more than one t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 7 publications
13
23
0
Order By: Relevance
“…Increase in female headed households is seen to increase the chance of being poor by about 62%; this might be in conformity with the assertion that female access less productive capital as compare to their male counterpart. The result is in line with the findings of Adeoti (2014). Also, more years of education is known to reduce poverty in the study area by 12.9% and an increase in the share of the dependents on the household head will raise poverty of the respondents.…”
Section: Determinants Of Poverty In Rural Nigeria In the Study Areasupporting
confidence: 89%
“…Increase in female headed households is seen to increase the chance of being poor by about 62%; this might be in conformity with the assertion that female access less productive capital as compare to their male counterpart. The result is in line with the findings of Adeoti (2014). Also, more years of education is known to reduce poverty in the study area by 12.9% and an increase in the share of the dependents on the household head will raise poverty of the respondents.…”
Section: Determinants Of Poverty In Rural Nigeria In the Study Areasupporting
confidence: 89%
“…This finding implies that the probability of being poor increases with age. The above is in consonance with the submissions of Adeoti (2014) and Amao et al (2017) who reported that age is a significant determinant of poverty across Nigeria. In the study area, the likelihood of being poor increases with being a female (rather than male).…”
Section: Factors Influencing Multidimensional Povertysupporting
confidence: 89%
“…Traditionally, poverty was considered a monetary issue, and hence, income was used as proxy for measuring it (Łuczka-Bakuła and Kalinowski, 2006;Adeoti, 2014). In recent past, the concepts of poverty have been broadened to include many other human development variables that are not necessarily economic in nature (Battiston et al, 2009;Le, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a number of studies such as Takane (2009), Berhanu (2011), Adeoti (2014) confirmed that there is a positive association between female household headship and the prevalence of poverty. However, there are still remaining unsettled issues among previous studies on the implications of female household headship on poverty.…”
Section: Introductionmentioning
confidence: 97%